Weaker cyclic (phi,phi)-contractive mappings with an application to integro-differential equations - Nashine, Hemant Kumar Kumar; Kadelburg, Zoran (Nonlinear Analysis: Modelling and Control, 2013)
We introduce a new variant of cyclic contractive mapping in a metric space and originate existence and uniqueness results of fixed points for such mappings. Examples are given to support the usability of our results. After these results, an application to integro-differential equations is given.
Keywords: fixed point; cyclic contraction; integro-differential equation